Pengaruh Disiplin Kerja dan Budaya Organisasi Terhadap Kinerja Operator Produksidi PT XXX - Rusda Irawati; Ezra Pelita Silalahi (Politeknik Negeri Batam, 2015)
The purposes of this research is to know the discipline and culture organization work on performance operator production in PT XXX. The technique of collecting data using questionnaires, observations and interviews. The total sample of 96 respondents to the department Glass Sensor as the research population. The analytical method used was multiple regression. The results showed that the influence of labor discipline on the performance of the operator, the influence of organizational culture on the performance of the operator, and the influence of labor discipline and organizational cultures together on the performance of the operator